2019
DOI: 10.3847/1538-4357/ab3a96
|View full text |Cite
|
Sign up to set email alerts
|

Preflare Processes, Flux Rope Activation, Large-scale Eruption, and Associated X-class Flare from the Active Region NOAA 11875

Abstract: We present a multi-wavelength analysis of the eruption of a hot coronal channel associated with an X1.0 flare (SOL2013-10-28T02:03) from the active region NOAA 11875 by combining observations from AIA/SDO, HMI/SDO, RHESSI, and HiRAS. EUV images at high coronal temperatures indicated the presence of a hot channel at the core of the active region from the early pre-flare phase evidencing the pre-existence of a quasi-stable magnetic flux rope. The hot channel underwent an activation phase after a localized and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 122 publications
1
16
0
Order By: Relevance
“…Therefore, the existence of prominence can be considered as an indicator of the magnetic FR in solar corona (Schmieder et al 2013;Filippov et al 2015). The relationship between the FR rise and associated radiative signatures has been a topic of considerable interest (e.g., Alexander et al 2006;Liu et al 2009b;Joshi et al 2013Joshi et al , 2016Mitra & Joshi 2019). In particular, comparisons of the location, timing, and strength of high-energy emissions (e.g., temporal and spatial evolution of HXR sources) with respect to the dynamical evolution of the prominence provide critical clues to help understand the characteristics of the underlying energy release phenomena, such as the expected site of magnetic reconnection, particle acceleration, and heating.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the existence of prominence can be considered as an indicator of the magnetic FR in solar corona (Schmieder et al 2013;Filippov et al 2015). The relationship between the FR rise and associated radiative signatures has been a topic of considerable interest (e.g., Alexander et al 2006;Liu et al 2009b;Joshi et al 2013Joshi et al , 2016Mitra & Joshi 2019). In particular, comparisons of the location, timing, and strength of high-energy emissions (e.g., temporal and spatial evolution of HXR sources) with respect to the dynamical evolution of the prominence provide critical clues to help understand the characteristics of the underlying energy release phenomena, such as the expected site of magnetic reconnection, particle acceleration, and heating.…”
Section: Introductionmentioning
confidence: 99%
“…Now, the appearance of 'classical' flare signatures, viz., distinct coronal and footpoint HXR sources along with inner flare ribbons formed at both sides of PIL, provide evidence of large-scale magnetic reconnection, which are attributed to the reconnection-opening of overlying field lines (i.e., progression of reconnection in higher coronal fields of the envelope region) stretched by the erupting MFR. The sudden transition in the kinematic evolution of MFR from the phase of slow to fast rise precisely divides the pre-flare and impulsive phase of the flare, which we attribute to the feedback relationship between the early CME dynamics and the strength of the large-scale magnetic reconnection (Temmer et al 2008;Vršnak 2016;Song et al 2018;Mitra & Joshi 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…The statistical studies carried out with SXR images from Yohkoh, revealed three categories of pre-flare activities in terms of source locations: co-spatial, adjacent, and remote (Fárník & Savy 1998;Kim et al 2008). The co-spatial and adjacent cases occurring within few minutes before the main flare are supposed to have direct relevance for the triggering processes related to the main flare (Liu et al 2009;Joshi et al 2011;Mitra & Joshi 2019). Notably, EUV and X-ray images clearly show that the pre-flare brightenings are spatially distributed along the hot channel (i.e., MFR) and within the core field region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flux ropes are defined by a set of magnetic field lines that are wrapped around each other in a braided fashion or wrapped around a central axis (braided and twisted flux ropes, respectively, see; Prior & Yeates 2016). Observationally, a flux rope can be identified in different forms: filament (Zirin 1988;Martin 1998), prominence (Tandberg-Hanssen 1995;Parenti 2014), coronal cavity (Forland et al 2013;Gibson 2015), hot channel (Zhang et al 2012;Cheng et al 2013;Mitra & Joshi 2019;Sahu et al 2020), coronal sigmoid (Rust & Kumar 1996;Manoharan et al 1996;Joshi et al 2017a;Mitra et al 2018) etc. The processes involved in the triggering of a flux rope from its stable condition and its successive evolution within the source region are rather complex and debatable (see e.g., Chatterjee & Fan 2013; Kumar et al 2016;Prasad et al 2020).…”
Section: Introductionmentioning
confidence: 99%